Iridium-modified nickel molybdenum oxide electrode and preparation method and application thereof

By introducing iridium single atoms into the nickel-molybdenum oxide electrode to improve its catalytic activity, the problems of high preparation cost and low catalytic efficiency of existing electrodes are solved, and high-efficiency electrolytic hydrogen production suitable for different pH conditions are achieved.

CN119753749APending Publication Date: 2025-04-04QILU INST OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510039953.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-10
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The existing electrodes used for electrolytic hydrogen production have high preparation cost and low catalytic efficiency.

Method used

Iridium modified nickel-molybdenum oxide electrode was used to prepare NiMoO4 electrode material by sol-gel method, and Ir single atoms were introduced into it to improve oxygen evolution performance.

Benefits of technology

It has achieved a low preparation cost and high catalytic activity iridium modified nickel-molybdenum oxide electrode, which is suitable for electrolytic hydrogen production under acidic, alkaline and neutral conditions, reducing its dependence on precious metals.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119753749A_ABST
    Figure CN119753749A_ABST
Patent Text Reader

Abstract

The invention discloses an iridium-modified nickel molybdenum oxide electrode and a preparation method and application thereof, and belongs to the technical field of electrode materials. According to the technical scheme, the preparation method comprises the following steps: dissolving NiSO4. 6H2O, (NH4) 6Mo7O24. 4H2O and citric acid in distilled water, then putting into an ice-water bath, adjusting the solution to be alkaline, drying to obtain xerogel, grinding the xerogel, and roasting to obtain NiMoO4 powder; the molar ratio of the NiSO4. 6H2O to the (NH4) 6Mo7O24. 4H2O to the citric acid is 7: 1: 50; the roasting temperature is any one value from 600 DEG C to 700 DEG C. The preparation method is applied to the aspect of electrode materials, solves the problems of high preparation cost and low catalytic efficiency of an existing electrode for electrolytic hydrogen production, and has the characteristics of low preparation cost and high catalytic activity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electrode materials, and in particular relates to an iridium-modified nickel-molybdenum oxide electrode, a preparation method and application thereof. Background Art

[0002] As a sustainable, clean and renewable energy source, hydrogen can not only alleviate the energy crisis caused by the limited reserves of traditional fossil fuels, but also solve the environmental pollution problems caused by the use of traditional fossil fuels. At present, the common methods for preparing hydrogen are: solar water decomposition hydrogen production method, electrocatalytic water decomposition hydrogen production method, nuclear energy hydrogen production method, biological hydrogen production method, fossil fuel hydrogen production method, and chemical hydride hydrogen production method. However, due to the high cost of preparation materials and serious pollution to the environment, it is difficult for them to be widely used in commercial applications. In contrast, electrocatalytic water decomposition hydrogen production method has higher safety, lower toxicity, and more complete technology.

[0003] Generally speaking, a water electrolysis system is a complex battery that includes a cathode and an anode. At the cathode, the hydrogen evolution reaction occurs, while at the anode, the oxygen evolution reaction occurs. However, the overpotential of the oxygen evolution reaction is very high because it involves the transfer of four electrons, making the reaction difficult. The main difficulty in producing hydrogen by seawater electrolysis lies in the chlorine evolution reaction at low pH values ​​and the chlorine oxidation reaction to produce hypochlorite at high pH values. Therefore, it is imperative to develop catalysts with high oxygen evolution activity, high selectivity, and large-scale production characteristics.

[0004] Currently, precious metal-based catalysts (IrO2 and RuO2) are still the best performers in catalysis; however, their scarce reserves, high prices and poor stability greatly limit their large-scale commercial applications. Summary of the invention

[0005] In view of the shortcomings of the prior art, the technical problem to be solved by the present invention is to overcome the problems of high preparation cost and low catalytic efficiency of the existing electrodes used for electrolysis of hydrogen, and to propose an iridium-modified nickel-molybdenum oxide electrode with low preparation cost and high catalytic activity, and a preparation method and application thereof.

[0006] In order to solve the technical problem, the technical solution adopted by the present invention is:

[0007] On the one hand, the present invention provides a method for preparing an iridium-modified nickel-molybdenum oxide electrode, comprising a NiMoO4 powder preparation step; the NiMoO4 powder preparation step comprises: mixing NiSO4·6H2O, (NH4)6Mo7O 24·4H2O and citric acid are dissolved in distilled water, then placed in an ice water bath, the solution is adjusted to alkaline, dried to obtain a dry gel, and the dry gel is ground and calcined to obtain NiMoO4 powder; the NiSO4·6H2O, (NH4)6Mo7O 24 The molar ratio of 4H2O to citric acid is 7:1:50; and the calcination temperature is any value between 600-700°C.

[0008] Preferably, in the step of preparing NiMoO4 powder, the solution is adjusted to a pH of 8-10 and the drying temperature is 55-65°C.

[0009] Preferably, the method further comprises the step of synthesizing Ir-NiMoO4 nanocrystals; the step of synthesizing Ir-NiMoO4 nanocrystals comprises: adding the NiMoO4 powder to an ethanol solution, ultrasonically treating the solution, slowly adding a H2IrCl6·6H2O solution, stirring and heating the mixture, drying the mixture, collecting the black powder and performing a heat treatment, and cooling the mixture to obtain Ir-NiMoO4 nanocrystals.

[0010] Preferably, in the step of synthesizing Ir-NiMoO4 nanocrystals, the mass ratio of the NiMoO4 powder to the ethanol solution is 1:20-1:5; and the amount ratio of the H2IrCl6·6H2O solution to the NiMoO4 powder is 1:32.

[0011] Preferably, in the step of synthesizing Ir-NiMoO4 nanocrystals, after adding the H2IrCl6·6H2O solution, the mixture is stirred and heated at 45-60°C for 4-5h, and the stirred and heated mixture is dried at 55-65°C for 4-6h.

[0012] Preferably, in the step of synthesizing Ir-NiMoO4 nanocrystals, black powder is collected and heat-treated at 400-450°C in an Ar atmosphere for 2-3 hours.

[0013] Preferably, it also includes an electrode preparation step; the electrode preparation step includes: preparing catalyst ink, preparing a NiMoO4 electrode with nickel foam as the matrix, or a NiMoO4 electrode with a titanium plate as the matrix, or an Ir-NiMoO4 electrode with nickel foam as the matrix, or an Ir-NiMoO4 electrode with a titanium plate as the matrix; the catalyst ink includes the NiMoO4 powder or the Ir-NiMoO4 nanocrystals.

[0014] Preferably, the size of the nickel foam and the titanium plate substrate is 1cm*0.2cm; the ink concentration is 40mg / mL; the solvent of the catalyst ink is 2.5wt% Nafion / ethanol solution; the mixing ratio of the NiMoO4 powder or the Ir-NiMoO4 nanocrystals and the ink is 8:2; during the electrode preparation process, a small amount is dripped each time, and the next dripping is carried out after it is evenly dispersed and dried at 60-65°C.

[0015] On the other hand, the present invention provides an iridium-modified nickel-molybdenum oxide electrode prepared by the preparation method of the iridium-modified nickel-molybdenum oxide electrode described in any of the above technical solutions, wherein the iridium-modified nickel-molybdenum oxide electrode is an Ir-NiMoO4 electrode with nickel foam as the matrix, or an Ir-NiMoO4 electrode with titanium plate as the matrix.

[0016] The present invention also provides the use of the iridium-modified nickel-molybdenum oxide electrode described in any of the above technical solutions in hydrogen production by electrolysis.

[0017] Compared with the prior art, the present invention has the following beneficial effects:

[0018] The invention provides a method for preparing an iridium-modified nickel-molybdenum oxide electrode, wherein a NiMoO4 electrode material catalyst is prepared by a sol-gel method, and a single Ir atom is further introduced into the NiMoO4 to improve the intrinsic oxygen evolution performance. The method has the characteristics of low preparation cost and high catalytic activity of the prepared iridium-modified nickel-molybdenum oxide electrode.

[0019] The present invention provides an iridium-modified nickel-molybdenum oxide electrode. Under acidic and alkaline conditions, the NiMoO4 electrode and the Ir-NiMoO4 electrode based on nickel foam show better oxygen evolution activity, but under neutral conditions, the NiMoO4 electrode and the Ir-NiMoO4 electrode based on titanium plate show better oxygen evolution activity, thereby achieving the successful preparation of non-precious metal catalysts, and trace doping of Ir can achieve a significant improvement in activity. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 The apparent oxygen evolution activity diagram of the Ir-NiMoO4 / NF electrode with the composition shown in Table 1 under alkaline conditions;

[0021] Figure 2 The apparent oxygen evolution activity diagram of the Ir-NiMoO4 / NF electrode with the composition shown in Table 1 under neutral conditions;

[0022] Figure 3 The apparent oxygen evolution activity diagram of the Ir-NiMoO4 / NF electrode with the composition shown in Table 1 under acidic conditions;

[0023] Figure 4This is the XRD pattern of the Ir-NiMoO4 electrode with the composition shown in Table 1. DETAILED DESCRIPTION

[0024] The technical scheme in the specific embodiment of the present invention is described in detail and completely below. Obviously, the described embodiment is only a part of the specific implementation of the overall technical scheme of the present invention, rather than all implementations. Based on the overall concept of the present invention, all other embodiments obtained by ordinary technicians in this field fall within the scope of protection of the present invention.

[0025] On the one hand, the present invention provides a method for preparing an iridium-modified nickel-molybdenum oxide electrode, comprising a NiMoO4 powder preparation step; the NiMoO4 powder preparation step comprises: mixing NiSO4·6H2O, (NH4)6Mo7O 24 ·4H2O and citric acid are dissolved in distilled water, then placed in an ice water bath, the solution is adjusted to alkaline, dried to obtain a dry gel, and the dry gel is ground and calcined to obtain NiMoO4 powder; the NiSO4·6H2O, (NH4)6Mo7O 24 The molar ratio of 4H2O to citric acid is 7:1:50; the calcination temperature is any value between 600-700°C. The preparation method prepares NiMoO4 powder by sol-gel method, and has the characteristics of low preparation cost. The above technical scheme specifically defines NiSO4·6H2O, (NH4)6Mo7O 24 · The molar ratio of 4H2O and citric acid is 600-700℃, because this specific molar ratio can ensure that the raw materials are fully and appropriately complexed and reacted in the reaction system, which is conducive to the formation of a uniform and stable sol, and then promotes the formation of a dry gel, which has a key influence on the purity, crystallinity and microstructure of the final NiMoO4 powder. If the molar ratio deviates from this range, it may lead to incomplete reaction of the raw materials, the formation of impurity phases or uneven gel structure, affecting the performance and quality of the product; the above technical scheme also specifically limits the calcination temperature, because the temperature range of 600-700℃ is more suitable for the crystal transformation, crystal growth and impurity removal of NiMoO4 powder. When the temperature is too low, the dry gel cannot be fully decomposed and converted into the target NiMoO4 crystal phase, and more impurities will remain and the crystallinity is poor; while too high a temperature may cause excessive crystal growth, agglomeration and even phase change, destroying the ideal microstructure and performance of the NiMoO4 powder, thereby affecting its catalytic activity, stability and other key characteristics in related applications. It can be understood that the calcination temperature may also be 620°C, 640°C, 660°C, 680°C, and any point within the range thereof.

[0026] In a preferred embodiment, in the step of preparing NiMoO4 powder, the solution is adjusted to a pH of 8-10 and the drying temperature is 55-65°C. The technical solution specifically limits the pH because in an alkaline environment of pH 8-10, it is helpful for metal ions (Ni 2+ and Mo 6+ ) forms a stable metal-organic complex with citric acid. This complex structure can better control the hydrolysis and polycondensation reaction rates in the subsequent sol-gel process, so that the generated sol has a more uniform particle size distribution and chemical composition, which is conducive to the formation of high-quality dry gel and the final acquisition of NiMoO4 powder with excellent performance and high purity. The drying temperature is also specifically limited because the drying temperature of 55-65°C can ensure that the solvent evaporates slowly and fully while avoiding the gel structure from shrinking too quickly or causing local thermal decomposition due to excessive temperature, thereby maintaining the porous structure and chemical uniformity of the gel, which is conducive to the uniform growth of NiMoO4 crystals and the formation of good crystalline morphology in the subsequent calcination process. Further, NH3·H2O is used to adjust the solution until the pH value reaches 8-10, the mixture is dried at 55-65°C for 24-48h, and the calcination temperature in the muffle furnace is 600-700°C, and the temperature is maintained for 4-4.5h at a gradient heating method of 5°C / min.

[0027] In a preferred embodiment, the method further includes the step of synthesizing Ir-NiMoO4 nanocrystals; the step of synthesizing Ir-NiMoO4 nanocrystals includes: adding the NiMoO4 powder to an ethanol solution, and then slowly adding a H2IrCl6·6H2O solution after ultrasonic treatment, stirring and heating the mixture, drying, collecting black powder and performing heat treatment, and cooling to obtain Ir-NiMoO4 nanocrystals. The technical solution specifies that the NiMoO4 powder is firstly mixed with the ethanol solution, and then the H2IrCl6·6H2O solution is slowly added, because the ethanol solution, as a dispersion medium, can make the NiMoO4 powder evenly dispersed, avoid agglomeration, and ensure that it has a larger contact area and active sites in subsequent reactions.

[0028] In a preferred embodiment, in the step of synthesizing Ir-NiMoO4 nanocrystals, the mass ratio of the NiMoO4 powder to the ethanol solution is 1:20-1:5; the dosage ratio of the H2IrCl6·6H2O solution to the NiMoO4 powder is 1:32. The technical solution specifically defines the dosage of each substance in the step of synthesizing Ir-NiMoO4 nanocrystals, because the precise dosage of the substance directly determines the composition ratio, crystal structure and final physical and chemical properties of the nanocrystals. The appropriate dosage ratio of NiMoO4 powder to H2IrCl6·6H2O and other substances can ensure that the effective doping or loading amount of iridium (Ir) atoms in the NiMoO4 lattice is in the optimal range, which not only avoids the failure to significantly improve the catalytic performance of the material due to too low Ir content, but also prevents agglomeration or changes in the crystal structure of NiMoO4 that is originally stable and conducive to catalytic reactions due to excessive Ir.

[0029] In a preferred embodiment, in the step of synthesizing Ir-NiMoO4 nanocrystals, after adding the H2IrCl6·6H2O solution, the mixture is stirred and heated at 45-60°C for 4-5h, and the stirred and heated mixture is dried at 55-65°C for 4-6h. In a preferred embodiment, in the step of synthesizing Ir-NiMoO4 nanocrystals, black powder is collected and heat-treated at 400-450°C in an Ar atmosphere for 2-3h.

[0030] In a preferred embodiment, it also includes an electrode preparation step; the electrode preparation step includes: preparing catalyst ink, preparing a NiMoO4 electrode with nickel foam as the matrix, or a NiMoO4 electrode with a titanium plate as the matrix, or an Ir-NiMoO4 electrode with nickel foam as the matrix, or an Ir-NiMoO4 electrode with a titanium plate as the matrix; the catalyst ink includes the NiMoO4 powder or the Ir-NiMoO4 nanocrystals.

[0031] In a preferred embodiment, the size of the nickel foam and the titanium plate substrate is 1cm*0.2cm; the ink concentration is 40mg / mL; the solvent of the catalyst ink is 2.5wt% Nafion / ethanol solution; the mixing ratio of the NiMoO4 powder or the Ir-NiMoO4 nanocrystals and the ink is 8:2; during the electrode preparation process, a small amount is dripped each time, and the next dripping is carried out after it is evenly dispersed and dried at 60-65°C.

[0032] On the other hand, the present invention provides an iridium-modified nickel-molybdenum oxide electrode prepared by the preparation method of the iridium-modified nickel-molybdenum oxide electrode described in any of the above technical solutions, wherein the iridium-modified nickel-molybdenum oxide electrode is an Ir-NiMoO4 electrode with nickel foam as the matrix, or an Ir-NiMoO4 electrode with titanium plate as the matrix.

[0033] The present invention also provides the use of the iridium-modified nickel-molybdenum oxide electrode described in any of the above technical solutions in electrolytic hydrogen production. Among them, under acidic and alkaline conditions, the NiMoO4 electrode and the Ir-NiMoO4 electrode based on nickel foam show better oxygen evolution activity, but under neutral conditions, the NiMoO4 electrode and the Ir-NiMoO4 electrode based on titanium plate show better oxygen evolution activity, achieving the successful preparation of non-precious metal catalysts, and the trace doping of Ir can achieve a significant increase in activity.

[0034] In order to more clearly and in detail introduce the iridium-modified nickel-molybdenum oxide electrode, its preparation method and application provided by the embodiments of the present invention, a description will be given below in conjunction with specific embodiments.

[0035] Example 1

[0036] NiMoO4 powder was synthesized by sol-gel method. 7mmol NiSO4·6H2O, 1mmol (NH4)6Mo7O 24 ·4H2O and 50mmol citric acid were dissolved in 20ml distilled water. Subsequently, the mixture was placed in an ice-water bath (ice cubes, water and salt to form an ice-water mixture), NH3·H2O was dripped into the above solution to adjust the pH of the solution to 8, and then the above mixture was dried to obtain a dry gel. Finally, the dry gel was fully ground in a mortar and transferred to a muffle furnace in several portions to prevent the dry gel from expanding during heating and falling into the muffle furnace. The sample was heated to 700℃ at a heating rate of 5℃ / min for a total of 4 hours.

[0037] Preparation of NiMoO4 / NF electrode. NiMoO4 catalyst powder and carbon powder were mixed in a ratio of 8:2 (the catalyst ink with a concentration of 40 mg / mL was used in the experiment) and then ground into fine powder in a mortar. 1 mL of 2.5 wt% Nafion / ethanol solution was added and ultrasonicated with an ultrasonic machine to mix it thoroughly. 10, 20, 30, 40, and 50 μL of the solution were drawn with a microinjector, i.e., the NiMoO4 loading was 2, 4, 6, 8, and 10 mg / cm, respectively. 2 , slowly drip a small amount each time on the substrate (1cm×0.2cm nickel foam), evenly spread it and dry it at 60℃, drip it one by one according to the above steps, and pay attention that the coating liquid cannot seep out of the edge. Take out the electrode and cool it naturally.

[0038] Electrode electrochemical performance test. The activity of NiMoO4 electrode based on nickel foam increases with the increase of loading, whether in acidic, alkaline or neutral conditions. The activity of the electrode under acidic conditions is generally higher than that under alkaline conditions, among which the activity of the electrode under neutral conditions is not ideal. The current density of NiMoO4 / NF electrode at 1.7 V (vs. RHE) under alkaline conditions is 9.25 times that under neutral conditions. Under acidic conditions, the current density of NiMoO4 / NF at 1.7 V (vs. RHE) is 23.72 times that under neutral conditions and 2.56 times that under alkaline conditions.

[0039] Example 2

[0040] NiMoO4 powder was synthesized by sol-gel method. 7mmol NiSO4·6H2O, 1mmol (NH4)6Mo7O 24 ·4H2O and 50mmol citric acid were dissolved in 20ml distilled water. Subsequently, the mixture was placed in an ice-water bath (ice cubes, water and salt to form an ice-water mixture), NH3·H2O was dripped into the above solution to adjust the pH of the solution to 8, and then the above mixture was dried to obtain a dry gel. Finally, the dry gel was fully ground in a mortar and transferred to a muffle furnace in several portions to prevent the dry gel from expanding during heating and falling into the muffle furnace. The sample was heated to 700℃ at a heating rate of 5℃ / min for a total of 4 hours.

[0041] Preparation of NiMoO4 / Ti electrode. NiMoO4 catalyst powder and carbon powder were mixed in a ratio of 8:2 (the catalyst ink with a concentration of 40 mg / mL was used in the experiment) and then ground into fine powder in a mortar. 1 mL of 2.5 wt% Nafion / ethanol solution was added and ultrasonicated with an ultrasonic machine to mix it thoroughly. 10, 20, 30, 40, and 50 μL of the solution were drawn with a microinjector, i.e., the NiMoO4 loading was 2, 4, 6, 8, and 10 mg / cm, respectively. 2 , slowly drip a small amount each time on the substrate (1cm×0.2cm nickel foam), evenly spread it and dry it at 60℃, drip it one by one according to the above steps, and pay attention that the coating liquid cannot seep out of the edge. Take out the electrode and cool it naturally.

[0042] Electrochemical performance test of the electrode. The activity of the NiMoO4 electrode based on the titanium plate increases with the increase of the loading amount regardless of whether it is acidic, alkaline or neutral. The activity of the NiMoO4 catalyst loaded on the titanium plate is generally higher under alkaline conditions than under acidic and neutral conditions, and the maximum current density of the electrode under acidic and neutral conditions does not reach 10mA / cm 2Compared with the electrode based on nickel foam, the current density of NiMoO4 / NF at 1.7V (vs. RHE) under alkaline conditions is 23.525mA / cm 2 The current density of NiMoO4 / NF at 1.7V (vs.RHE) under alkaline conditions increased by 53.7%. The current density of NiMoO4 / NF at 1.7V (vs.RHE) under acidic conditions was 60.324mA cm -2 , which is 33.5 times the current density of NiMoO4 / Ti at 1.7V (vs.RHE) under acidic conditions.

[0043] Example 3

[0044] NiMoO4 powder was synthesized by sol-gel method. 7mmol NiSO4·6H2O, 1mmol (NH4)6Mo7O 24 ·4H2O and 50mmol citric acid were dissolved in 20ml distilled water. Subsequently, the mixture was placed in an ice-water bath (ice cubes, water and salt to form an ice-water mixture), NH3·H2O was dripped into the above solution to adjust the pH of the solution to 8, and then the above mixture was dried to obtain a dry gel. Finally, the dry gel was fully ground in a mortar and transferred to a muffle furnace in several portions to prevent the dry gel from expanding during heating and falling into the muffle furnace. The sample was heated to 700℃ at a heating rate of 5℃ / min for a total of 4 hours.

[0045] Synthesis of Ir-NiMoO4 nanocrystals. Add 0.5g NiMoO4 to 10mL ethanol solution and obtain a well-dispersed mixture after ultrasonic treatment for 5min. Then, slowly add 1.920ml H2IrCl6·6H2O solution dropwise with a magnetic stirrer. Finally, heat the mixture with magnetic stirring at 50℃ for 4h, and then place it in a 60℃ oven for drying until the ethanol is completely evaporated. Then transfer the collected black powder to a porcelain boat and heat treat it at 400℃ in a muffle furnace for 2h. After cooling naturally to room temperature, collect the powder.

[0046] Preparation of Ir-NiMoO4 / NF electrode. Ir-NiMoO4 catalyst powder and carbon powder were mixed in a ratio of 8:2 (the catalyst ink with a concentration of 40 mg / mL was used in the experiment) and then ground into fine powder in a mortar. 1 mL of 2.5 wt% Nafion / ethanol solution was added and ultrasonicated with an ultrasonic machine to mix it thoroughly. 10, 20, 30, 40, and 50 μL of the solution were drawn with a microinjector, i.e., the Ir-NiMoO4 loading was 2, 4, 6, 8, and 10 mg / cm, respectively. 2, slowly drip a small amount each time on the substrate (1cm×0.2cm nickel foam), evenly spread it and dry it at 60℃, drip it one by one according to the above steps, and pay attention that the coating liquid cannot seep out of the edge. Take out the electrode and cool it naturally.

[0047] Electrode electrochemical performance test. The activity of Ir-NiMoO4 electrode based on nickel foam increases with the increase of loading amount, whether in acidic, alkaline or neutral conditions. The activity of the electrode under alkaline conditions is generally higher than that under acidic and neutral conditions. The loading amount is 10mg / cm 2 , the current density analysis at 1.7V shows that the current density of the electrode under alkaline conditions increased by 46.6% compared with the electrode under acidic conditions, and increased by 97.0% compared with the electrode under neutral conditions, indicating that the electrode has better oxygen evolution performance under alkaline conditions. The current density of Ir-NiMoO4 / NF under alkaline conditions increased by 470% compared with NiMoO4 / NF, the current density of Ir-NiMoO4 / NF under neutral conditions increased by 59% compared with NiMoO4 / NF, and the current density of Ir-NiMoO4 / NF under acidic conditions increased by 18.5% compared with NiMoO4 / NF.

[0048] Example 4

[0049] NiMoO4 powder was synthesized by sol-gel method. 7mmol NiSO4·6H2O, 1mmol (NH4)6Mo7O 24 ·4H2O and 50mmol citric acid were dissolved in 20ml distilled water. Subsequently, the mixture was placed in an ice-water bath (ice cubes, water and salt to form an ice-water mixture), NH3·H2O was dripped into the above solution to adjust the pH of the solution to 8, and then the above mixture was dried to obtain a dry gel. Finally, the dry gel was fully ground in a mortar and transferred to a muffle furnace in several portions to prevent the dry gel from expanding during heating and falling into the muffle furnace. The sample was heated to 700℃ at a heating rate of 5℃ / min for a total of 4 hours.

[0050] Synthesis of Ir-NiMoO4 nanocrystals. Add 0.5g NiMoO4 to 10mL ethanol solution and obtain a well-dispersed mixture after ultrasonic treatment for 5min. Then, slowly add 1.920ml H2IrCl6·6H2O solution dropwise with a magnetic stirrer. Finally, heat the mixture with magnetic stirring at 50℃ for 4h, and then place it in a 60℃ oven for drying until the ethanol is completely evaporated. Then transfer the collected black powder to a porcelain boat and heat treat it at 400℃ in a muffle furnace for 2h. After cooling naturally to room temperature, collect the powder.

[0051] Preparation of Ir-NiMoO4 / Ti electrode. Ir-NiMoO4 catalyst powder and carbon powder were mixed in a ratio of 8:2 (the concentration used in the experiment was 40 mg mL -1 The catalyst ink) was ground into fine powder in a mortar, and 1 mL of 2.5 wt% Nafion / ethanol solution was added and ultrasonicated by an ultrasonic machine to mix it thoroughly. 10, 20, 30, 40, and 50 μL of the solution were drawn with a microinjector, i.e., the Ir-NiMoO4 loading was 2, 4, 6, 8, and 10 mg / cm, respectively. 2 , slowly drip a small amount each time on the substrate (1cm×0.2cm titanium plate), evenly spread it and dry it at 60℃, drip it one by one according to the above steps, and pay attention that the coating liquid cannot seep out of the edge. Take out the electrode and cool it naturally.

[0052] Electrode electrochemical performance test. The electrochemical oxygen evolution activity analysis of the Ir-NiMoO4 electrode based on titanium plate found that the activity of the electrode increased with the increase of the loading amount regardless of acidic, alkaline or neutral conditions. The activity of the Ir-NiMoO4 catalyst loaded on the titanium plate is generally higher under alkaline conditions than under acidic and neutral conditions. The current density of the Ir-NiMoO4 / Ti electrode under alkaline conditions reached 75.955mA / cm at 1.7 (vs.RHE). 2 The current density of Ir-NiMoO4 / Ti electrode under acidic conditions is 6.596 mA / cm at 1.7 (vs. RHE). 2 The current density of Ir-NiMoO4 / Ti electrode at 1.7 (vs. RHE) under neutral conditions is 9.896 mA / cm 2 Compared with the Ir-NiMoO4 electrode based on nickel foam, the current density under alkaline conditions decreased by 76.4%.

[0053] Performance Testing

[0054] The electrode composition shown in Table 1 was tested for its electrochemical performance. The test results are shown in Figure 1 , 2 , 3, 4. Related tests include linear sweep voltammetry test, cyclic voltammetry test, double layer capacitance test, etc. Among them, the electrolytes in the linear sweep voltammetry test are 0.5mol / L H2SO4, 1mol / LKOH solution and PBS solution, which correspond to the acidic, alkaline and neutral systems of the electrochemical test respectively. The chlorine evolution electrolyte of the chlorine evolution reaction is 4mol / LNaCl solution (pH=1). The linear sweep voltammetry test is carried out at a scan rate of 5mV / s. The scanning range of the linear sweep voltammetry test is 1.00-1.80V (vs.RHE), and the working electrode area in the test is 0.2cm 2The electrolytes for the cyclic voltammetry test are 0.5 mol / L H2SO4, 1 mol / L KOH solution and PBS solution, which correspond to the acidic, alkaline and neutral systems of the electrochemical test respectively. The cyclic voltammetry test is carried out at a scan rate of 100 mV / s. The scan range of the cyclic voltammetry test is 0-1.4 V (vs. RHE). The scan rate range for the double layer capacitance test is 10-100 mV / s.

[0055] Table 1 Loading composition of Ir-NiMoO4 electrode

[0056]

[0057]

[0058] Depend on Figure 4 As shown, it can be clearly seen that the diffraction peaks observed at 44.4°, 51.5° and 76.0° correspond to the (111), (200) and (220) crystal planes of Ni, respectively. The surface diffraction peaks of Mo at 40.8°, 59.0° and 74.1°, and the surface diffraction peaks of Ir at 41.0°, 47.6°, 69.9° and 84.0° cannot be observed. In the figure, the diffraction peaks at 40.1°, 52.3°, 62.7° and 70.2° correspond to the (101), (102), (110) and (103) crystal planes of the Ti matrix, respectively. This corresponds to the fact that the Ni loading in the XRF analysis is much higher than that of Mo and Ir.

Claims

1. A method for preparing an iridium-modified nickel-molybdenum oxide electrode, characterized in that: The method comprises the steps of preparing NiMoO4 powder; the steps of preparing NiMoO4 powder comprising: NiSO4·6H2O, (NH4)6Mo7O 24 ·4H2O and citric acid are dissolved in distilled water, then placed in an ice water bath, the solution is adjusted to alkaline, dried to obtain a dry gel, and the dry gel is ground and calcined to obtain NiMoO4 powder; the NiSO4·6H2O, (NH4)6Mo7O 24 The molar ratio of 4H2O to citric acid is 7:1:50; and the calcination temperature is any value between 600-700°C.

2. The method for preparing the iridium-modified nickel-molybdenum oxide electrode according to claim 1, characterized in that: In the NiMoO4 powder preparation step, the solution is adjusted to a pH of 8-10 and the drying temperature is 55-65°C.

3. The method for preparing the iridium-modified nickel-molybdenum oxide electrode according to claim 1, characterized in that: Also included is a step of synthesizing Ir-NiMoO4 nanocrystals; The step of synthesizing Ir-NiMoO4 nanocrystals comprises: The NiMoO4 powder is added to an ethanol solution, and after ultrasonic treatment, a H2IrCl6·6H2O solution is slowly added, the mixture is stirred and heated, and then dried, black powder is collected and heat-treated, and after cooling, Ir-NiMoO4 nanocrystals are obtained.

4. The method for preparing the iridium-modified nickel-molybdenum oxide electrode according to claim 3, characterized in that: In the step of synthesizing Ir-NiMoO4 nanocrystals, the mass ratio of the NiMoO4 powder to the ethanol solution is 1:20-1:5; the amount ratio of the H2IrCl6·6H2O solution to the NiMoO4 powder is 1:

32.

5. The method for preparing the iridium-modified nickel-molybdenum oxide electrode according to claim 3, characterized in that: In the step of synthesizing Ir-NiMoO4 nanocrystals, after adding the H2IrCl6·6H2O solution, the mixture is stirred and heated at 45-60°C for 4-5 hours, and the stirred and heated mixture is dried at 55-65°C for 4-6 hours.

6. The method for preparing the iridium-modified nickel-molybdenum oxide electrode according to claim 3, characterized in that: In the step of synthesizing Ir-NiMoO4 nanocrystals, black powder is collected and heat-treated at 400-450°C in an Ar atmosphere for 2-3 hours.

7. The method for preparing the iridium-modified nickel-molybdenum oxide electrode according to claim 3, characterized in that: The electrode preparation step is also included; the electrode preparation step includes: Catalyst ink is prepared to prepare a NiMoO4 electrode based on nickel foam, a NiMoO4 electrode based on a titanium plate, an Ir-NiMoO4 electrode based on nickel foam, or an Ir-NiMoO4 electrode based on a titanium plate; the catalyst ink includes the NiMoO4 powder or the Ir-NiMoO4 nanocrystals.

8. The method for preparing the iridium-modified nickel-molybdenum oxide electrode according to claim 7, characterized in that: The size of the nickel foam and the titanium plate substrate is 1cm*0.2cm; the ink concentration is 40mg / mL; the solvent of the catalyst ink is 2.5wt% Nafion / ethanol solution; the mixing ratio of the NiMoO4 powder or the Ir-NiMoO4 nanocrystals and the ink is 8:2; during the electrode preparation process, a small amount is dripped each time, and the next dripping is carried out after it is evenly dispersed and dried at 60-65°C.

9. The iridium-modified nickel-molybdenum oxide electrode prepared by the method for preparing the iridium-modified nickel-molybdenum oxide electrode according to any one of claims 1 to 8, characterized in that: The iridium-modified nickel-molybdenum oxide electrode is an Ir-NiMoO4 electrode based on nickel foam or an Ir-NiMoO4 electrode based on a titanium plate.

10. Use of the iridium-modified nickel-molybdenum oxide electrode according to claim 9 in hydrogen production by electrolysis.